2023
DOI: 10.3389/fpubh.2023.1165662
|View full text |Cite
|
Sign up to set email alerts
|

Modifiable determinants of central obesity among the rural black population in the DIMAMO HDSS, Limpopo, South Africa

Abstract: BackgroundCentral obesity is a leading risk factor for cardiometabolic diseases, in which body fat accumulates to a particular extent, and may negatively impact on health. The prevalence of abdominal obesity has increased over the last 10 years and currently surpasses that of overall obesity. There is a scarcity of data on the determinants of central obesity, especially among populations residing in rural Africa. The aim of the present study was thus to determine sociodemographic and lifestyle factors that are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
1
0
0
Order By: Relevance
“…However, this could perhaps be due to the fact that majority of respondents in this study were single. The findings of this study go in line with a study done by (Ntimana & Choma, 2023) whereby Bivariate correlation analysis showed that married participants correlated positively and significantly with central obesity. Similarly, a study Bakir et al, (2017) reported that the mean Body mass indexes and other anthropometric measurements such as Waist circumference were significantly higher in married women.…”
Section: Anthropometric Status Of University Students Central Obesity...supporting
confidence: 91%
“…However, this could perhaps be due to the fact that majority of respondents in this study were single. The findings of this study go in line with a study done by (Ntimana & Choma, 2023) whereby Bivariate correlation analysis showed that married participants correlated positively and significantly with central obesity. Similarly, a study Bakir et al, (2017) reported that the mean Body mass indexes and other anthropometric measurements such as Waist circumference were significantly higher in married women.…”
Section: Anthropometric Status Of University Students Central Obesity...supporting
confidence: 91%